2016
DOI: 10.1105/tpc.16.00062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity of Terpene Synthases in the Liverwort Marchantia polymorpha

Abstract: Marchantia polymorpha is a basal terrestrial land plant, which like most liverworts accumulates structurally diverse terpenes believed to serve in deterring disease and herbivory. Previous studies have suggested that the mevalonate and methylerythritol phosphate pathways, present in evolutionarily diverged plants, are also operative in liverworts. However, the genes and enzymes responsible for the chemical diversity of terpenes have yet to be described. In this study, we resorted to a HMMER search tool to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 81 publications
(103 reference statements)
2
59
0
Order By: Relevance
“…Intriguingly, a recently identified monofunctional KS from the liverwort Marchantia polymorpha (MpKS) (Kumar et al, 2016) was found to contain an Ile at the key position previously identified in spermatophyta KSs ( Figure 1 ). Moreover, this Ile is further conserved in the only characterized KS from a lycophyte (i.e., Selaginella moellendorffii , SmKS) (Shimane et al, 2014), as well as the bifunctional CPS/KSs identified from other bryophytes (Hayashi et al, 2006; Kawaide et al, 2011).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Intriguingly, a recently identified monofunctional KS from the liverwort Marchantia polymorpha (MpKS) (Kumar et al, 2016) was found to contain an Ile at the key position previously identified in spermatophyta KSs ( Figure 1 ). Moreover, this Ile is further conserved in the only characterized KS from a lycophyte (i.e., Selaginella moellendorffii , SmKS) (Shimane et al, 2014), as well as the bifunctional CPS/KSs identified from other bryophytes (Hayashi et al, 2006; Kawaide et al, 2011).…”
Section: Resultsmentioning
confidence: 77%
“…The enzymes investigated here are pseudomature constructs suitable for recombinant expression in Escherichia coli , as previously described for MpKS (Kumar et al, 2016), PpCPS/KS (Hayashi et al, 2006), OsKSL5i (Xu et al, 2007a), and AtKS (Yamaguchi et al, 1998). Site-directed mutants were constructed by whole-plasmid PCR amplification of the relevant pENTR/SD/d-TOPO constructs using the primers described in Supplementary Table S1, and AccuPrime TM Pfx DNA Polymerase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to low yields and difficulties in detection and isolation, the presence of terpenoids in the metabolites of bacteria, particularly actinomycetes, is likely to be overlooked. However, an in‐depth understanding of genome sequence of terpenes and the progress in fermentation and isolation provided the stimulus for the isolation of a large number of bacterial terpene metabolites …”
Section: Introductionmentioning
confidence: 99%